The essential structure of patients’ experience of rehabilitation with emphasis on their self reported needs in the context of rehabilitation : a phenomenological study - Jónína Sigurgeirsdóttir (2006)
Verkefnið er opið nemendum og starfsfólki Háskólans á Akureyri Reflection on patients’ needs is a necessary part of the assessment of quality of services. An interpretive phenomenological study aimed to add to the existing knowledge base about the phenomenon patients’ needs in rehabilitation, the patients’ side was explored, which is, unfortunately, a rare perspective in rehabilitation literature. The sample was purposively selected and consisted of twelve individuals aged 26-85 years -seven men, five women - who had experienced rehabilitation therapy at one of three main rehabilitation clinics in Iceland. The participants were seen as co-researchers and their medical diagnoses were heart disease, paralysis, arthritis, chronic lung disease, stroke, chronic fatigue, psychological problems and pain. Six co-researchers had been referred to rehabilitation following an acute event and six because of a chronic state. The study was conducted in accordance with The Vancouver School of Doing Phenomenology and each co-researcher was interviewed one to three times. The end result was sixteen in-depth interviews that were analyzed thematically and interpreted. Six main needs were identified in the co-researchers’ accounts. Firstly, the coresearchers needed to be able to cope with the impact of their acute or chronic problems. They felt that their ability to cope was strongly tied to their own personal traits, their earlier experience and preconceptions, knowing the source of their suffering, and to experience a balance between sleep, rest and activity while in rehabilitation. Secondly, they needed to adapt to a new self since their accident or illness usually meant adapting to new characteristics of self. They needed, however, in the middle of these existential changes to be able to sustain a personal role and needed faith, hope and optimism to succeed. Thirdly, they needed individualized caring, where they needed to be ‘I’ and not just ‘the patient’, they needed to be listened to and heard in a caring relationship where ...